2021
DOI: 10.1016/j.mtbio.2021.100128
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible copper sulfide–based nanocomposites for artery interventional chemo-photothermal therapy of orthotropic hepatocellular carcinoma

Abstract: Transcatheter arterial embolization has been considered as a promising targeted delivery approach for hepatocellular carcinoma (HCC). Currently, chemoembolization was the main treatment for unresectable HCC. However, the traditional chemoembolization treatment suffers from undesirable therapeutic effects and serious side-effects. In this study, the doxorubicin (DOX)-encapsulated and near-infrared (NIR)–responsible copper sulfide (CuS)–based nanotherapeutics was developed for magnetic resonance imaging (MRI)–gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Earlier, Kelly et al ( 175 ) successfully used hematoporphyrin derivatives as photosensitizers in the treatment of bladder cancer, creating a precedent for the application of PDT on tumors. The traditional DDSs relying on photosensitizers have limited application for the PDT of tumors, owing to their poor pharmacokinetics ( 176 , 177 ) and long-term biological safety issues ( 176 178 ). For example, MoS2 DDSs, the biotoxicity of which is caused by quantum size effects and surface effects, may have adverse effects on the human reproductive system ( 178 ).…”
Section: Application Of Ph-responsive Polymer Nanomaterials In Tumor ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Kelly et al ( 175 ) successfully used hematoporphyrin derivatives as photosensitizers in the treatment of bladder cancer, creating a precedent for the application of PDT on tumors. The traditional DDSs relying on photosensitizers have limited application for the PDT of tumors, owing to their poor pharmacokinetics ( 176 , 177 ) and long-term biological safety issues ( 176 178 ). For example, MoS2 DDSs, the biotoxicity of which is caused by quantum size effects and surface effects, may have adverse effects on the human reproductive system ( 178 ).…”
Section: Application Of Ph-responsive Polymer Nanomaterials In Tumor ...mentioning
confidence: 99%
“…For example, MoS2 DDSs, the biotoxicity of which is caused by quantum size effects and surface effects, may have adverse effects on the human reproductive system ( 178 ). Previous studies have shown that nanomaterial drug carriers have a higher uptake rate of tumor cells and fewer side effects ( 177 ), and the specific response of drugs to the tumor can be further enhanced by designing stimulus-responsive nano-drug carriers.…”
Section: Application Of Ph-responsive Polymer Nanomaterials In Tumor ...mentioning
confidence: 99%
“…Local high temperature through near-infrared light is also an effective strategy to enhance the efficacy of CDT ( Zhou et al, 2019 ; Li et al, 2021b ). For example, Jin et al (2020) recently reported dual-targeted core-shell nanoplatforms (PTFHD nanoplatforms) for photothermal therapy (PTT) enhanced CDT.…”
Section: Ht Enhanced M-cdt Nanodrugsmentioning
confidence: 99%
“…In recent years, photothermal therapy (PTT), as a specific emerging cancer therapy, has been extensively researched in the field of tumor treatment (Liu et al, 2019;Danewalia and Singh, 2021). Many transition metal nanomaterials have been researched for PTT, such as MoS 2 -based nanomaterials (Jianling , CoS 2 nanomaterials (Wang et al, 2020a), copper-based nanomaterials (Ai et al, 2021;Wang et al, 2021b;Li et al, 2021), titanium-based nanomaterials (Wang et al, 2020b;Wang et al, 2021c), covalent organic frameworks (COFs) (Yao et al, 2021b), etc. Compared with above PTT agents, Bi 2 X 3 -based nanomaterials have been proven to be a kind of more excellent photosensitizers due to the strong near-infrared absorption performance and high photothermal conversion efficiency of Bi 2 X 3 (Xie et al, 2016;Cheng et al, 2018).…”
Section: Photothermal-enhanced Radiotherapymentioning
confidence: 99%